2017
DOI: 10.1002/acm2.12230
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric‐modulated arc therapy versus intensity‐modulated radiotherapy for large volume retroperitoneal sarcomas: A comparative analysis of dosimetric and treatment delivery parameters

Abstract: PurposeTo compare dosimetric and treatment delivery parameter differences between volumetric‐modulated arc radiotherapy (VMAT) and intensity‐modulated radiotherapy (IMRT) for large volume retroperitoneal sarcomas (RPS).Materials and MethodsBoth VMAT and IMRT planning were performed on CT datasets of 10 patients with RPS who had been previously treated with preoperative radiotherapy. Plans were optimized to deliver ≥95% dose to the PTV and were evaluated for conformity and homogeneity. Dose to the organs at ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Among other factors included in the multivariate analyses, increasing values of heart V 5 and heart V 30 in the high dose group might best explain why patients administered a high dosage of radiation did worse than the patients who were administered a standard dosage of radiation. Several studies demonstrated that VMAT could reduce delivery time and MUs compared with IMRT (21)(22)(23). Reduction in delivery time has the potential of decreasing the uncertainty occurred during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among other factors included in the multivariate analyses, increasing values of heart V 5 and heart V 30 in the high dose group might best explain why patients administered a high dosage of radiation did worse than the patients who were administered a standard dosage of radiation. Several studies demonstrated that VMAT could reduce delivery time and MUs compared with IMRT (21)(22)(23). Reduction in delivery time has the potential of decreasing the uncertainty occurred during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies, this study found that the ability to deliver higher RT dose to both a TE and a non-TE group might be associated with HT advantages. A dosimetric study of RPS with large CTV confirmed the superiority of HT for dose uniformity compared to step-and-shoot IMRT (9,26). In addition, HT is optimized for image guidance using megavoltage CT (MVCT) images in an IMRT era where importance of image guidance is more emphasized (27).…”
Section: Discussionmentioning
confidence: 99%
“…It is now endorsed by the American Society for Radiation Oncology (ASTRO), American Society for Clinical Oncology (ASCO) and American Urology Association (AUA). 11,12 This cost-effective approach reduces hospital stays and visits and allows radiation R Ra ad di io ot th he er ra ap py y f fo or r R Ra ad di ic ca al l T Tr re ea at tm me en nt t Pak Armed Forces Med J 2023; 73(3): 911 facilities to treat more patients simultaneously. On the other hand, using a higher dose per fraction could lead to increased toxicity of neighbouring OARs, especially bladder and rectum, in the case of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%